Periodic Acid, a Novel Oxidant of Polycyclic, Aromatic Hydrocarbons - Fatiadi, Alexander J. (J Res Natl Bur Stand A Phys Chem, 1968)
Certain polycyclic, aromatic hydrocarbons can be oxidized with periodic acid in aprotic solvents containing a small proportion of water. A unique, two-fold character of response to periodic acid by these hydrocarbons has been found: (1) production of a coupling reaction through a radical intermediate [conversion of pyrene into 1,1′-bipyrene, and fluorene into 1,2-bis(2,2′-biphenylylene)ethylene] or (2) conversion into quinones by a two-equivalent oxidation mechanism that does not involve a radical intermediate [acenaphthene, anthracene, anthrone, benz[a]anthracene, naphthacene, naphthalene, and phenanthrene]. Little or no reaction was observed when oxidation was attempted with sodium metaperiodate instead of periodic acid. Electron-spin resonance revealed no radical intermediate in the oxidation of malonic acid with either periodic acid or sodium periodate.